Children’s Navigation of Contextual Cues in Peer Transgressions: The Role of Aggression Form, Transgressor Gender, and Transgressor Intention - Yuly-Youngblood, Andrea C.; Caporaso, Jessica S.; Croce, Rachel C.; Boseovski, Janet J. (Frontiers in Psychology, 2022)
When faced with transgressions in their peer groups, children must navigate a series of situational cues (e.g., type of transgression, transgressor gender, transgressor intentionality) to evaluate the moral status of the transgressions and to inform their subsequent behavior toward the transgressors. Little is known about which cues children prioritize when presented together, how reliance on these cues may be affected by certain biases (e.g., gender norms), or how the prioritization of these cues may change with age. To explore these questions, 138 5- to 7-year-olds (younger children) and 8- to 10-year-olds (older children) evaluated a series of boy and girl characters who partook in physical or relational aggression with ambiguous or purposeful intent. Children were asked to provide sociomoral evaluations (i.e., acceptability, punishment, and causal attribution judgments) and social preferences. Transgressor gender only impacted children’s social preferences. Conversely, aggression form and transgressor intent shifted children’s sociomoral judgments: they were harsher toward physical transgressors with purposeful intent over those with ambiguous intent but made similar evaluations for relational transgressors regardless of intentionality. The present results suggest that gender is perhaps not uniformly relevant to children across all contexts, as other cues were prioritized for children’s sociomoral judgments. Since children likely have less familiarity with relational aggression compared to physical aggression, it follows that intent would only shift judgments about physical transgressors. This research provides insight about how children simultaneously navigate multiple cues in aggression contexts, which is likely reflective of their real-world experiences.